2021
DOI: 10.1016/j.amjoto.2021.102999
|View full text |Cite
|
Sign up to set email alerts
|

Cranial nerve involvement in COVID-19

Abstract: Introduction The COVID-19 disease emerged in Wuhan province of China in November 2019 and spread across the world in a short time, resulting in a pandemic. The first case in Turkey was detected on March 11, 2020. The aim of the current study was to reveal the effects of COVID-19 on cranial nerves by monitoring people infected with the disease based on repeated examinations and surveys. Material and method The data of 356 patients with a positive COVID-19 polymerase chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 24 publications
1
36
0
Order By: Relevance
“…Researchers from Europe have reported a high prevalence of dysphonia due to COVID-19 disease with a prevalence of 26.8% by Lechien et al and 43.7% by Cantarella et al [ 5 , 6 ]. However, scarce studies, mainly in form of case reports or low prevalence of dysphonia, were reported from other parts of the world [ [7] , [8] , [9] ]. Consistently with these observations, this research was aimed to determine the prevalence of dysphonia in patients with COVID-19 disease and to assess the demographic, clinical, and outcome of these subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers from Europe have reported a high prevalence of dysphonia due to COVID-19 disease with a prevalence of 26.8% by Lechien et al and 43.7% by Cantarella et al [ 5 , 6 ]. However, scarce studies, mainly in form of case reports or low prevalence of dysphonia, were reported from other parts of the world [ [7] , [8] , [9] ]. Consistently with these observations, this research was aimed to determine the prevalence of dysphonia in patients with COVID-19 disease and to assess the demographic, clinical, and outcome of these subjects.…”
Section: Introductionmentioning
confidence: 99%
“…19 Direct neuroinvasion may occur by the virus entering the cell using ACE-2 receptors. 20 On the other hand, in indirect mechanism, SARS-CoV-2 infection triggers the immune system, stimulating production of a plethora of antibodies. Some of which may have autoimmune properties towards neural proteins, causing parainfectious or postinfectious immune-mediated nerve injury.…”
Section: Discussionmentioning
confidence: 99%
“…[1] The incubation period of COVID-19 is around five days in the initial stage of the disease, and although the most common complaints are fever, cough, myalgia, headache, and joint pain, patients can also present with many different symptoms, including taste and smell disorders, diarrhea, and weakness. [2] The COVID-19 disease caused by the SARS-CoV2 virus commonly results in cranial nerve symptoms. The fact that these findings are more common and severe in COVID-19 than previous SARS and MERS outbreaks suggests that it has a more neurotrophic and more aggressive neuroinvasion.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that these findings are more common and severe in COVID-19 than previous SARS and MERS outbreaks suggests that it has a more neurotrophic and more aggressive neuroinvasion. [2] In this context, we aimed to discuss a case report of acute isolated bilateral abducens nerve palsy following SARS-CoV-2 infection. All patients gave informed consent for the publication of their case details and any accompanying images.…”
Section: Introductionmentioning
confidence: 99%